Measurement of the 241Am(n,2n) Reaction Cross Section, by the Activation Method - Perdikakis, G.; et al., - (HNPS Advances in Nuclear Physics, 2020)
The measurement of the cross section of the reaction 241Am(n,2n)240Am, has been performed, for the first time at neutron energies of 8.8, 9.6, 10.6 and 11.4 MeV, by the activation method. The monoenergetic neutron beam was produced at the 5.5MV TANDEM accelerator of NCSR "Demokritos", using the H{d,n) He reaction. During the 5-day long irradiation, the neutron flux was monitored by a BF3, counter. The neutron yield as well as the beam current, were recorded in 100 sec intervals by two multiscaling units. The radioactive target consisted of a 37GBq 241Am source enclosed in a Pb container. A natural Au foil, 27Al foil and a 93Nb foil were used as reference materials for the neutron flux determination. The activity of the irradiated targets, was measured off-line by a 56% relative efficiency, HPGe detector. The first preliminary results are presented and compared with evaluated libraries and existing data.